Retargeting the management of hypercholesterolemia – focus on evolocumab - Colletti A; Derosa G; Cicero AFG (Dove Medical Press, 2016)
Alessandro Colletti,1 Giuseppe Derosa,2 Arrigo FG Cicero1 1Department of Medical and Surgical Sciences, University of Bologna, Bologna, 2Department of Internal Medicine and Therapeutics, University of Pavia and Policlinico San Matteo Foundation, Pavia, Italy Abstract: Hypercholesterolemia is one of the main risk factors for atherosclerosis and cardiovascular diseases. The treatment is based on the modification of the diet and lifestyle and if necessary on a pharmacological therapy. The most widely used drugs are the inhibitors of 3-hydroxy-3-methyl-glutaryl coenzyme A reductase (statins); nevertheless, many patients do not reach optimal levels of low-density lipoprotein-cholesterol (LDL-C) even with maximal dosage of statins (eventually associated to ezetimibe) or present side effects, which do not allow them to continue the treatment. Inhibitors of PCSK9 represent a new therapeutic approach for lowering LDL-C. Evolocumab and alirocumab are human monoclonal antibodies, which bind to extracellular PCSK9 and thus interfere with the degradation of low-density lipoprotein receptor. Evolocumab use is approved for the treatment of patients with heterozygous familial hypercholesterolemia (FH) and homozygous FH as an adjunct to diet and maximally tolerated statin therapy or for subjects with clinical atherosclerotic cardiovascular disease who require additional lowering of LDL-C. Phase III clinical trials have demonstrated the effectiveness of evolocumab (140 mg/every 2 weeks or 420 mg/month, via subcutaneous injection) in monotherapy and in combination with statins, in the treatment of patients intolerant to statins or with FH. In monotherapy, it reduces LDL-C by 55%, and its association with statins leads to a reduction of LDL-C by up to 63%–75%. Evolocumab has been demonstrated to be safe and well tolerated. Ongoing clinical trials are assessing the long-term effects of evolocumab on the incidence of cardiovascular risk, safety, and tolerability. This review resumes the available clinical evidence on the efficacy and safety of evolocumab, for which a relatively large amount of clinical data are currently available, and discusses the retargeting of cholesterol-lowering therapy in clinical practice. Keywords: PCSK9, hyperlipidemia, evolocumab, LDL-C, familial hypercholesterolemia